THE DAILY 110 MHZ SURVEY (BSA FIAN) IN THE ON-LINE MODE: DATABASE AND PROCESSING ETHODS - Samodurov, V. A.; Kitaeva, M. A.; Logvinenko, S. V.; Isaev, E. .; Dumsky, D. V.; Pugachev, V. D. (Одеські астрономічні публікації, 2014)
From 2012 on radio telescope BSA FIAN multi beams diagram was started. It capable at July 2014 daily observing by 96 beams in declination -8 .. 42 degrees in the frequency band 109-111.5 MHz. The number of frequency bands are from 6 to 32, the time constant are from 0.1 to 0.0125 sec. In receiving mode with 32 band (plus one common band) with a time constant of 12.5 ms (80 times per second) respectively produced 33x96x80 four byte real and so daily we produced 87.5 Gbt (yearly to 32 Tbt). These data are enormous opportunities for both short and long-term monitoring of various classes of radio sources (including radio transients) and for space weather and the Earth’s ionosphere monitoring, for search for different classes of radio sources, etc.